Sistem Notifikasi Kondisi Angin Menggunakan Metode Fuzzy untuk Keselamatan Pelayaran - Kresna Wiska Kafila; Dahnial Syauqy; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
A ship accident is an issue that happens every year. From the investigation data of cruise accident - KNKT 2010-2016 recorded 337 victims died and 474 wounded. The data does not include unregistered and unrecorded fishermen. Factors that cause the occurrence of cruise accidents is a strong wind conditions. The strong winds causes an increase in sea wave height. In this research using two parameters these are wind speed of the rotary encoder module and wind direction of dual axis module. The parameters are then processed using the fuzzy method. The output of the system is a safety level notification based on parameter readings these are safe, alert and dangerous. Based on testing, the system has an accuracy of 95.37% at wind speed, has an average difference of degree 4,29018o in wind direction, and has a match result between the fuzzy system output with the expected output.